THE EFFECT OF THE USING OF DIFFERENT ANTIMICROBIAL INGREDIENTS ON THE QUALITY OF FRESH CATFISH (Pangasius hypophthalmus) DURING STORAGE AT COLD TEMPERATURE (±5°C) - Romauli Nababan; N.Ira Sari; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the effect of the using of different antimicrobial ingredients (extracts of starfruit leaves, starfruit fruit, and liquid smoke) on the quality of catfish during storage at cold temperature (± 5°C). The method used was the experimental method, composed for non-factorial randomized block design (RBD), and consisting of 4 kinds of the treatment, namely: without antimicrobial agents, starfruit leaf extract 10%, starfruit meat extract 10%, and liquid smoke solution 10 %. All treatments were stored at cold temperature (±5°C), observed in the first day 6 days and 12 days, and evaluated for the total plate count (TPC), the existence of Escherichia coli and Salmonella sp., pH value and organoleptic value (the score of appearance, odor, and texture). The results showed that the best quality of fresh catfish was produced by thetreatment  of the using of 10% starfruit leaf extract. It was indicated by the lowest number of total bacteria (TPC) at 5.2 x 104Cfu / g, the number of Coliform at 3.0 MPN/g, Escherichia coli bacteria and Salmonella sp. were negative, and the lowest pH value at 6.64 after 12 days of storage. The organoleptic evaluation of the catfish was showing the eye appearance value 6.4, withcharacteristic rather bright, the eyeball is flat, the pupil is rather gray, and the cornea is somewhat cloudy; the gill value 6.5, withcharacteristic of the mucus layer began to be somewhat cloudy, rather white color, and less transparent; the meat value 6.04, withthe characteristic of slightly less bright, specific typical species, no milking along the spine and intact abdominal wall; the texture value 5.9with the characteristic of the meat quite dense, elastic when pressed with fingers, and the flesh was difficult to tear separated from the spine; and the odor value 6.04 with the characteristic of fresh odor,typical fresh fish odor after storing for 6 days.  Keywords: Catfish, Pangasius hypophthalmus, Antimicrobials, storage, cold temperatures